THE ROLE OF SUSTAINABLE LEADERSHIP IN ENCOURAGING GREEN BUSINESS PRACTICES AT PERUM BULOG PALOPO BRANCH - Fajar Dap; Rismawati Rismawati; Rahmad Solling Hamid (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to explore the influence of sustainable leadership within BULOG and its alignment with green business practices. Employing a qualitative method of descriptive analysis, the research follows a three-step procedure for data analysis, which encompasses data reduction, data display, and conclusion derivation. Triangulation, a method involving the examination of data using different approaches from the same source, is adopted to ensure data credibility. The findings indicate that sustainable leadership plays a pivotal role in bolstering green business initiatives within BULOG's Palopo Branch. Additionally, the results highlight that sustainability considerations are seamlessly integrated into the company's operational framework, fostering an environment conducive to a green economy